Photogrammetric refinement of laser-based building roof contours - Dal Poz, Aluir Porfirio [UNESP] (My University, 2013)
In this paper a photogrammetric method is proposed for refining 3D building roof contours extracted from airborne laser scanning data. It is assumed that laser-derived planar faces of roofs are potentially accurate, while laser-derived building roof contours are not well defined. First, polygons representing building roof contours are extracted from a high-resolution aerial image. In the sequence, straight-line segments delimitating each building roof polygon are projected onto the corresponding laser-derived roof planes by using a new line-based photogrammetric model. Finally, refined 3D building roof contours are reconstructed by connecting every pair of photogrammetrically- projected adjacent straight lines. The obtained results showed that the proposed approach worked properly, meaning that the integration of image data and laser scanning data allows better results to be obtained, when compared to the results generated by using only laser scanning data. © 2013 IEEE.
Keywords: 3d buildings; Airborne Laser scanning; Building roof; High-resolution aerial images; Integration of images; Laser scanning data; Laser-based; Straight-line segments; Buildings; Laser applications; Photogrammetry; Remote sensing; Three dimensional; Roofs